Evaluation of the programme to reduce vulnerability in coastal fishing areas in Djibouti: Qualitative findings - Eissler, Sarah; Heckert, Jessica (International Food Policy Research Institute, 2024)
We present findings from a qualitative study conducted as part of an impact assessment of the Programme to Reduce Vulnerability in Coastal Fishing Areas (PRAREV) , supported by the International Fund for Agricultural Development (IFAD) and implemented from 2013 to 2021. This study was designed to focus solely on the gender aspects of PRAREV, which overall aimed to support fishing communities and actors in the fishing sector in Djibouti, specifically those living in rural coastal areas affected by climate change, by reducing their vulnerability to the effects of climate change and promote co-management of marine resources. The program targeted those who are poor and who rely on fishing, particularly women involved in fish processing and marketing. The qualitative findings shared in this paper complement findings from an accompanying quantitative study, which found positive effects of the program on incomes, production, women’s influence on decisions, and food security, but not on resilience or nutritional status.